EFFECT OF EXTERNAL ENVIRONMENT ORGANIZATION AND APPLICATION OF TOTAL QUALITY MANAGEMENT (TQM) AND PERFORMANCE OF THE COMPANY AND ITS EFFECT ON COMPETITIVE ADVANTAGE IN PTISM BOGASARI FLOURMILLS, JAKARTA - Mawarti, Ana Retno (Fakultas Ekonomi, Universitas Negeri Jakarta, 2016)
This research aimed to discover the impact of external environment and Total Quality Management implementation on company performance in order to create competitive advantage in PT. ISM Bogasari Flourmills. This research is an associative explanatory research with quantitative method. The data sources used are primary data and secondary data. The primary data collected by spreading 122 questionnaires to employees of PT. ISM Bogasari on chief officers level, assistant manager level, and manager level. Sampling method used is Proportionable Stratified Random Sampling. The result showed that external environment with indicator of complexity, dynamics and environment carrying capacity, has positive and significant impact on company’s performance. Total Quality Management implementation with indicators of costumer focus, continuous refinement and staff training program, brings positive and significant impact on company’s performance. The company’s performance with its indicators of efficiency, effectiveness, and adaptability, has positive and significant impact on the creation of competitive advantage. The Research also proved that external environment and Total Quality Management Implementation directly affect the creation of competitive advantage. Keywords: External environment, Total Quality Management implementation, company’s performance, and competitive advantage